La imagen de la lepra en las Cantigas de Santa María de Alfonso X El Sabio - Morente Parra, Maribel (Anales de Historia del Arte, 2007)
The appearance of lepers in a repertoire of miracles like the Cantigas de Santa María, reflects on the one hand, the constant presence of the disease like one of the evils that punished the medieval population, and on the other hand, the necessity of the mariana intercession like road of physical and spiritual salvation. The iconographic identity given to the leprosy allows us to individualize the disease like the integral part of a whole: the evil.